1993
DOI: 10.1063/1.110417
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier on n-type GaN grown by hydride vapor phase epitaxy

Abstract: A Schottky barrier on unintentionally doped n-type GaN grown by hydride vapor phase epitaxy was obtained and characterized. Using vacuum evaporated gold as the Schottky barrier contact and aluminum for the ohmic contact, good quality diodes were obtained. The forward current ideality factor was n∼1.03 and the reverse bias leak current below 1×10−10 A at a reverse bias of −10 V. The barrier height φBn was determined to be 0.844 and 0.94 eV by current-voltage and capacitance measurements, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
159
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(173 citation statements)
references
References 5 publications
12
159
1
1
Order By: Relevance
“…Previous reports have attributed variations in the fitted Richardson constant to enhanced tunneling current, interfacial oxide layers, or lateral Schottky barrier height variation. [17][18][19][20][21][22][23] However, since we find that the current of the higher TDD sample is always lower than the current of the lower TDD sample at all forward bias voltages, it is unlikely that tunneling is responsible for the deviation, since an additional parallel transport mechanism will only add current in forward bias as would any regions of reduced barrier heights associated with the higher dislocation density. The similarity of the barrier heights and ideality factors for both types of samples supports the assertion that tunneling is negligible and that an interfacial layer is absent.…”
Section: B Reconciliation Of the Richardson Constant And Impact Of Tmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous reports have attributed variations in the fitted Richardson constant to enhanced tunneling current, interfacial oxide layers, or lateral Schottky barrier height variation. [17][18][19][20][21][22][23] However, since we find that the current of the higher TDD sample is always lower than the current of the lower TDD sample at all forward bias voltages, it is unlikely that tunneling is responsible for the deviation, since an additional parallel transport mechanism will only add current in forward bias as would any regions of reduced barrier heights associated with the higher dislocation density. The similarity of the barrier heights and ideality factors for both types of samples supports the assertion that tunneling is negligible and that an interfacial layer is absent.…”
Section: B Reconciliation Of the Richardson Constant And Impact Of Tmentioning
confidence: 87%
“…It shows that a review of the literature reveals many reports of large variations in the extracted Richardson constant for n-GaN Schottky diodes using simple I-V models with reported values ranging from 0.006 to 102 A K −2 cm −2 . [17][18][19] This large variation is reported despite the fact that the Richardson constant is a fundamental parameter that depends only on the semiconductor material constants, and thus should not display significant dependencies on Schottky metal, TDD, etc. This calls into question the simple extraction of Richardson constants as is commonly done in I-V analysis as described in Sec.…”
Section: B Reconciliation Of the Richardson Constant And Impact Of Tmentioning
confidence: 99%
“…From thermionic emission theory, I 0 is given by The significant difference could be due to the existence of a very thin SiO 2 barrier at the ZnO:N/ p-Si interface, through which the electrons must tunnel, as discussed by Hacke et al in connection with the much lower value of A ‫ء‬ found on n-GaN Schottky barrier diodes. 13 Interestingly, the forward current at higher biases, where the current is limited by series resistance, decreases as temperature decreases. The reason may well involve carrier freeze-out in the ZnO:N layer, which has been confirmed by temperature-dependent measurements of dark current in a ZnO:N layer grown on sapphire in a separate run.…”
Section: Resultsmentioning
confidence: 99%
“…Since the thickness of the standoff region sets the resistivity of the device, it will determine power dissipation and maximum current density of the device. 2,3 In previous studies, Schottky diodes have been fabricated on GaN using a variety of elemental metals including Pd and Pt, 4,5 , Au, Cr, and Ni,6,7 , and Mo and W. 8 More details on the metal-GaN contact technology can be found in Ref. 9.…”
mentioning
confidence: 99%